2013
DOI: 10.1017/s0960258512000268
|View full text |Cite
|
Sign up to set email alerts
|

Underdeveloped embryos and kinds of dormancy in seeds of two gymnosperms: Podocarpus costalis and Nageia nagi (Podocarpaceae)

Abstract: Although it has been speculated that seeds of the gymnosperm family Podocarpaceae have an underdeveloped embryo, no detailed studies have been done to definitively answer this question. Our purpose was to determine if embryos in seeds of two species of Podocarpaceae, Podocarpus costalis and Nageia nagi, from Taiwan are underdeveloped and to examine the kind of dormancy the seeds have. Embryos in fresh seeds of P. costalis were 4.6^0.5 mm long, and they increased in length by about 54% before radicle emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Therefore, we have confirmed that seeds of these two species have non-deep simple MPD. These results are similar to those reported by Walck et al (1999) on seeds of Thalictrum mirabile, by Hidayati et al (2000) on seeds of Lonicera morrowii, and by Chen et al (2013) on seeds of Nageia nagi.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we have confirmed that seeds of these two species have non-deep simple MPD. These results are similar to those reported by Walck et al (1999) on seeds of Thalictrum mirabile, by Hidayati et al (2000) on seeds of Lonicera morrowii, and by Chen et al (2013) on seeds of Nageia nagi.…”
Section: Discussionsupporting
confidence: 91%
“…The mean germination time (MGT) for both cytotypes varied across the cultivars and induced lines and was clearly not accurate in explaining the role of ploidy in seed germination. Although some researchers have used the MGT to evaluate the seed vigour of many plants (Matthews et al, 2012;Chen et al, 2013), other studies found the MGT to be inaccurate arguing that seeds can have different final germination percentage and have the same MGT because seeds can germinate across a different spread (Kader, 2005). The MGT expressed better the day, in which most of the seeds germinated in a seed lot or accurately defined the mean lag period between the start of imbibition and germination for each seed (Matthews, Khajeh-Hosseini, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that the B. napus variety with the high dormancy would lead to a long-term volunteer emergence in comparison with the low dormancy variety, but the annual seedling emergence was lower in the high dormancy variety (Huang et al ., 2016b). It is well known that seed dormancy can increase time to germination by increasing the time needed to break dormancy prior to germination (Roberts and Smith, 1977; Benech-Arnold et al ., 1990; Vleeshouwers, 1998; Chen et al ., 2013). The current study showed that the time to 50% of seedling emergence was 5.3 and 15.4 days longer in the MSD and the HSD seeds, respectively, after induction of secondary dormancy (Fig.…”
Section: Discussionmentioning
confidence: 99%